A micron In and nano Cu@Ag core-shell hybrid material interconnection process

Through the interconnection process of micro-In and nano-Cu@Ag core-shell hybrid materials, the problem of traditional interconnection materials being easily oxidized or migrated at high temperatures is solved, low-temperature connection and high-temperature service are achieved, interconnection temperature and conditions are reduced, and product reliability is improved.

CN115410934BActive Publication Date: 2025-04-18HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210853994.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-20
Publication Date
2025-04-18
Estimated Expiration
2042-07-20

AI Technical Summary

Technical Problem

Traditional chip-mounted interconnect materials are difficult to meet the high-temperature working conditions of third-generation power semiconductor devices, and nano-Ag and nano-Cu materials are prone to oxidation or migration at high temperatures, affecting product reliability.

Method used

The interconnection process of micro-In and nano-Cu@Ag core-shell mixed materials is adopted, and the mixture of nano-Cu@Ag particles and micro-In particles is treated through ultrasonic and vacuum drying to reduce the porosity and pores of the joints, and low-temperature connection and high-temperature service are achieved through hot press sintering or electromagnetic induction sintering technology.

Benefits of technology

Low-temperature connection and high-temperature service are achieved, interconnection temperature and conditions are reduced, pores and holes in joints are reduced, electrical conductivity, thermal conductivity and shear resistance of the welds are improved, and product reliability is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115410934B_ABST
    Figure CN115410934B_ABST
Patent Text Reader

Abstract

The present invention discloses a micron In and nano Cu@Ag core-shell mixed material interconnection process, the process comprising the following steps: step one: preparation of micron In and nano Cu@Ag core-shell mixed solder paste; step two: substrate processing; step three: solder paste coating / printing; step four: hot pressing / electromagnetic induction sintering. Micron In and nano Cu@Ag core-shell can cooperate with each other, make full use of space, reduce porosity, can greatly reduce the cost of raw materials, and play a huge advantage in industrial mass production. The present invention can achieve low-temperature connection and high-temperature service, not only reduces the interconnection temperature and interconnection conditions, but also effectively reduces the pores and holes in the joints, can interconnect the chip and the substrate under low-temperature and pressureless conditions, complete the connection and packaging of semiconductor devices, and can be well applied to the manufacture of semiconductor devices and microelectronic packaging, power electronics packaging and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic packaging micro-interconnection, and relates to a micron In and nano Cu@Ag core-shell mixed material interconnection process for low-temperature connection and high-temperature service. Background Art

[0002] With the rapid development of third-generation power semiconductor devices such as silicon carbide (SiC) and gallium nitride (GaN), their operating temperatures can reach as high as 250°C to 300°C. Traditional chip mounting interconnection materials are difficult to meet the conditions for their high-temperature operation, and new alternative materials are urgently needed. Due to the size effect of metal nanomaterials, the melting point of metal nanoparticles decreases as the size of the nanoparticles decreases, so that they can be sintered and formed at a temperature far below the melting point of the bulk. At the same time, nanomaterials can work stably for a long time at higher temperatures after sintering, which well meets the needs of "low-temperature sintering and high-temperature service" and is an ideal chip interconnection material. Nano-Ag has a low sintering temperature and a high service temperature. It has excellent electrical and thermal conductivity, strong corrosion resistance and oxidation resistance, but its electromigration and chemical migration phenomena are serious, which can easily lead to short-circuit failure of the circuit, which will seriously affect the reliability of the product. Nano-Cu is very easy to oxidize, and the generated oxides will increase the sintering temperature and affect the electrical and thermal conductivity of the solder joint.

[0003] To solve the above problems, researchers have prepared nano Cu@Ag core-shell structures. The structural characteristics of the core Cu and the shell Ag can give full play to the advantages of the two materials and meet the requirements of improving the anti-migration of silver and enhancing the oxidation resistance of copper, but the nano core-shell material should have a large porosity and the problem of holes. Summary of the invention

[0004] In view of the above problems existing in the existing nano Cu@Ag core-shell materials, the present invention provides a hybrid interconnection process of micron In and nano Cu@Ag core-shell materials for low-temperature connection and high-temperature service. The hybrid interconnection process of the present invention reduces the porosity and holes of the joint, and greatly reduces the interconnection temperature and interconnection conditions while ensuring the conductivity of the interconnection material.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A micron In and nano Cu@Ag core-shell hybrid material interconnection process includes the following two technical solutions:

[0007] Technical solution 1:

[0008] Step 1: Preparation of micron In and nano Cu@Ag core-shell mixed solder paste

[0009] Step 1: Weigh a certain amount of dry micron In particles, pour them into the nano Cu@Ag core-shell particle solution, centrifuge after ultrasonication and place in a vacuum drying oven, and dry at room temperature for 4 h under -1 MPa vacuum conditions;

[0010] Step 1 and 2, placing the dried nano Cu@Ag core-shell particles and micron In particles mixed powder in a mortar, adding an appropriate amount of organic dispersant, grinding them fully to make them mixed evenly and grinding them into a paste, to obtain a micron In and nano Cu@Ag core-shell mixed solder paste, wherein: the organic dispersant can be one or a mixture of polyethylene glycol-400, ethanol, butanol, ethylene glycol and propylene glycol, the mass percentage of nano Cu@Ag core-shell particles and micron In particles in the mixed powder is 70~95%:5~30%, and the mass percentage of the mixed powder and the organic dispersant in the mixed solder paste is 80~90%:10%~20%;

[0011] Step 2: Substrate processing

[0012] Step 21: Use acetone to remove oil stains on the surface of the substrate, and use dilute hydrochloric acid to remove surface oxides;

[0013] Step 22: After drying, the cleaned substrate is polished to further remove the surface oxide film;

[0014] Step 23: Place the treated substrate in a vacuum drying oven and store it at room temperature under a vacuum condition of -1 MPa;

[0015] Step 3: Solder paste coating

[0016] Step 3: 1. Evenly apply the micron In and nano Cu@Ag core-shell mixed solder paste on the substrate treated in step 4 by screen printing, wherein the coating thickness of the micron In and nano Cu@Ag core-shell mixed solder paste on the substrate is 50-200 μm;

[0017] Step 32: Place the substrate coated with solder paste in a constant temperature drying oven and preheat it at 110-140 °C for 5-30 min to remove some of the remaining anhydrous ethanol in the solder paste to avoid the formation of more pores in the sintered structure;

[0018] Step 4: Hot Pressing and Sintering

[0019] The chip is placed on the solder paste to form a sandwich structure, and then placed in a hot press for sintering, wherein: the heating method adopts double-sided heating, the temperature rise rate is 4~6 ℃ / min, the pressure is 1~10 MPa, the heating temperature is 300~400 ℃, and the heating time is 5~30 min;

[0020] Technical solution 2:

[0021] Step 1: Preparation of micron In and nano Cu@Ag core-shell mixed solder paste

[0022] Step 1: Weigh a certain amount of dry micron In particles, pour them into the nano Cu@Ag core-shell particle solution, centrifuge after ultrasonication and place in a vacuum drying oven, and dry at room temperature for 4 h under -1 MPa vacuum conditions;

[0023] Step 1 and 2, placing the dried nano Cu@Ag core-shell particles and micron In particles mixed powder in a mortar, adding an appropriate amount of organic dispersant, grinding them fully to make them mixed evenly and grinding them into a paste, to obtain a micron In and nano Cu@Ag core-shell mixed solder paste, wherein: the organic dispersant can be one or a mixture of polyethylene glycol-400, ethanol, butanol, ethylene glycol and propylene glycol, the mass percentage of nano Cu@Ag core-shell particles and micron In particles in the mixed powder is 70~95%:5~30%, and the mass percentage of the mixed powder and the organic dispersant in the mixed solder paste is 80~90%:10%~20%;

[0024] Step 2: Substrate processing

[0025] Step 21: Use acetone to remove oil stains on the surface of the substrate, and use dilute hydrochloric acid to remove surface oxides;

[0026] Step 22: After drying, the cleaned substrate is polished to further remove the surface oxide film;

[0027] Step 23: Place the treated substrate in a vacuum drying oven and store it at room temperature under a vacuum condition of -1 MPa;

[0028] Step 3: Printing of solder paste

[0029] Place the mask in the center of the substrate, use a medicine spoon to evenly apply the nano Cu@Ag and micron In mixed solder paste on the substrate surface, and use a scraper to flatten the solder paste surface and scrape off the excess solder paste to obtain a printed substrate, where the micron In and nano Cu@Ag core-shell mixed solder paste is applied to a thickness of 60-80μm on the substrate;

[0030] Step 4: Electromagnetic Induction Sintering

[0031] The printed substrate and chip are assembled into a sandwich structure, a certain pressure is applied to the assembled sandwich structure sample, and it is placed on the upper end of the output copper tube of the electromagnetic induction heating equipment for rapid sintering, where: the heating power is 24~28KW, the sintering time is 10~30s, and the applied pressure is 1~10MPa.

[0032] In the present invention, the preparation method of nano Cu particles is an existing technology, and can be prepared by liquid phase reduction method, electrolysis method, solvent thermal method and the like. Taking liquid phase reduction method as an example, the specific preparation method is as follows:

[0033] At room temperature and pressure, under normal pressure with a temperature not higher than 100°C or under hydrothermal conditions, a redox reaction occurs in an alkaline solution between a soluble copper salt (such as copper sulfate, copper acetate, etc.) and a reducing agent (such as hydrazine hydrate, ascorbic acid, sodium borohydride, formaldehyde, etc.) to obtain nano Cu particles. The morphology and size of the nano Cu particles can be controlled by adjusting the pH value of the solution, the concentration of the soluble copper salt, the reaction time and the reaction temperature.

[0034] In the present invention, the preparation method of nano Cu@Ag core-shell is an existing technology, and can be prepared by replacement method, composite chemical plating, chemical reduction and other methods. Taking the replacement method as an example, the specific preparation method is as follows: first, the nano Cu particles are pre-treated before plating to remove the oxide film and oil stains on the surface, and then the nano Cu@Ag core-shell particles are obtained by replacement reaction, wherein the specific replacement method is as follows: a silver ammonia complex solution (or an EDTA complex solution) is added to the dispersion system of nano Cu particles, and a replacement reaction occurs on the surface of the nano Cu particles to form a Cu@Ag core-shell particle solution.

[0035] Compared with the prior art, the present invention has the following advantages:

[0036] 1. The melting point of In in the micron In particles and nano Cu@Ag core-shell hybrid material is only 156.6 °C, so it can be connected at a lower reflux temperature. When In is completely consumed to form intermetallic compounds, its service temperature increases. Therefore, low-temperature connection and high-temperature service can be achieved.

[0037] 2. In, Ag and Cu can generate intermetallic compounds to improve the spreading performance of the solder, so it has a faster reaction speed compared to the traditional Transient Liquid Phase (TLP) connection.

[0038] 3. Micron In and nano Cu@Ag core-shell can cooperate with each other, make full use of space, reduce porosity, significantly reduce the cost of raw materials, and play a huge advantage in industrial mass production.

[0039] 4. In, Ag and Cu can all generate intermetallic compounds to improve the strength of the joint. After the reaction is completed, the internal Cu core still exists. Compared with the traditional full IMCs (Intermetallic Compound) weld, the Cu core can better absorb external stress, thereby alleviating local stress concentration and improving the shear resistance of the weld. In addition, since Cu has good electrical and thermal conductivity, the electrical and thermal conductivity of the weld finally formed is also greatly improved compared with the traditional full IMCs weld.

[0040] 5. The present invention can realize low-temperature connection and high-temperature service, which not only reduces the interconnection temperature and interconnection conditions, but also effectively reduces the pores and holes formed in the joints. The chip and the substrate can be interconnected under low-temperature and pressure-free conditions to complete the connection and packaging of semiconductor devices. It can be well applied to the manufacture of semiconductor devices and microelectronic packaging, power electronic packaging and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Schematic diagram of sintering of printed micron In particles and nano Cu@Ag core-shell mixed solder paste. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0043] Embodiment 1:

[0044] This embodiment provides a process for interconnecting micron In particles and nano Cu@Ag core-shell mixed materials. Nano Cu particles are prepared by liquid phase reduction method, and then nano Cu@Ag core-shell materials are prepared by replacement method, and mixed with micron In particles to finally obtain nano Cu@Ag core-shell and micron In mixed solder paste. The nano Cu@Ag core-shell and micron In mixed solder paste is printed on a substrate, and the printed substrate and chip are assembled into a sandwich structure to obtain an integral device, and the integral device is sintered under a certain pressure to obtain an interconnected device. The specific implementation steps are as follows:

[0045] Step 1: Preparation of nano Cu particles. At room temperature and pressure, copper sulfate and hydrazine hydrate undergo redox reaction in an alkaline solution with a pH value of 12 to obtain nano Cu particles.

[0046] Step 2: Preparation of nano Cu@Ag. The nano Cu particles prepared in step 1 are first subjected to pre-plating treatment to remove the oxide film and oil stains on the surface, and then nano Cu@Ag particles are obtained through a replacement reaction.

[0047] Step 3: Weigh a certain amount of dry micron In particles, pour them into the nano Cu@Ag particle solution, centrifuge after ultrasonication and place in a vacuum drying oven for drying. Then put the dried nano Cu@Ag and micron In particle mixed powder in a mortar, add an appropriate amount of polyethylene glycol-400, fully grind it to mix evenly and grind it into a paste. The mass percentage of nano Cu@Ag core-shell particles and micron In particles in the mixed powder is 80%:20%, and the mass percentage of the mixed powder and organic dispersant in the mixed solder paste is 85%:15%.

[0048] Step 4: Substrate treatment. First, use acetone to remove the oil on the surface of the substrate, and use dilute hydrochloric acid to remove the surface oxide. After drying, the cleaned substrate copper plate is polished with 1000 # and 2000 # sandpaper in turn, which can further remove the surface oxide film and increase the surface roughness to facilitate the wetting of the solder paste. The treated substrate is stored in a vacuum drying oven.

[0049] Step 5: The micron In and nano Cu@Ag core-shell mixed solder paste is evenly coated on the substrate by screen printing, and the thickness of the solder paste is about 80μm. Then it is placed in a constant temperature drying oven and preheated at 140℃ for 10 minutes to remove some of the residual anhydrous ethanol in the solder paste to avoid the formation of more pores in the sintered structure.

[0050] Step 6: Place the copper chip on the solder paste to form a sandwich structure, and put it into the hot press. The heating method uses double-sided heating. Compared with single-sided heating, the sample is heated more evenly and can reduce thermal stress. The selected temperature rise rate is 5 ℃ / min, the pressure is 5 MPa, the heating temperature is 300 ℃, and the heating time is 30 min.

[0051] Embodiment 2:

[0052] The present embodiment is different from the embodiment 1 in that: in step 1, copper sulfate and hydrazine hydrate are subjected to an oxidation-reduction reaction in an alkaline solution with a pH value of 12 under heating conditions at 80° C. in a water bath to obtain nano Cu particles.

[0053] Embodiment 3:

[0054] The difference between this embodiment and embodiment 1 is that in step 3, after the prepared nano Cu@Ag particles and micron In particles are washed and centrifuged, the supernatant is poured out and placed in a vacuum drying oven for drying. Then the two particles are weighed in a certain proportion, placed in an agate mortar, fully ground for a certain period of time to make them evenly mixed, and then a proper amount of organic dispersant is added to grind them into a paste.

[0055] Embodiment 4:

[0056] The difference between this embodiment and embodiment 1 is that in step 3, a planetary gravity mixer is used to mix the weighed polyethylene glycol-400 and the powder at a speed of 1000 r / min for 80 s to obtain a mixed slurry.

[0057] Embodiment 5:

[0058] The difference between this embodiment and embodiment 1 is that in step five, the mask is placed in the center of the substrate, a spoon is used to evenly apply the nano-Cu@Ag and micro-In mixed solder paste on the surface of the substrate, and a scraper is used to flatten the surface of the solder paste and scrape off excess solder paste to obtain a printed substrate.

[0059] Embodiment 6:

[0060] The difference between this embodiment and embodiment 1 is that in step 6, the heating temperature is 350° C. and the heating time is 30 min.

[0061] Embodiment 7:

[0062] The difference between this embodiment and embodiment 1 is that in step 6, the heating temperature is 350° C. and the heating time is 60 min.

[0063] Embodiment 8:

[0064] The difference between this embodiment and embodiment 1 is that in step 6, the heating temperature is 300° C. and the heating time is 60 min.

[0065] Embodiment 9:

[0066] The difference between this embodiment and embodiment 1 is that in step 6, the heating temperature is 400° C. and the heating time is 30 min.

[0067] Embodiment 10:

[0068] The difference between this embodiment and embodiment 1 is that in step 6, the heating temperature is 400° C. and the heating time is 60 min.

[0069] Embodiment 11:

[0070] The difference between this embodiment and embodiment 1 is that in step 6, the heating temperature is 350° C. and the heating time is 30 min.

[0071] Embodiment 12:

[0072] The difference between this embodiment and embodiment 1 is that in step six, electromagnetic heating equipment is used for sintering, the heating power is 26 kW, the sintering time is 15 s, and the applied pressure is 5 MPa.

Claims

1. A micron In and nano Cu@Ag core-shell hybrid material interconnection process, characterized in that The process comprises the following steps: Step 1: Preparation of micron In and nano Cu@Ag core-shell mixed solder paste Step 1: Weigh the dried micron In particles, pour them into the nano Cu@Ag core-shell particle solution, centrifuge after ultrasonication and dry them in a vacuum drying oven; Step 1 and 2, placing the dried nano Cu@Ag core-shell particles and micron In particles mixed powder in a mortar, adding an organic dispersant, grinding them fully to make them evenly mixed and grinding them into a paste to obtain a micron In and nano Cu@Ag core-shell mixed solder paste; Step 2: Substrate processing Step 21: Use acetone to remove oil stains on the surface of the substrate, and use dilute hydrochloric acid to remove surface oxides; Step 22: After drying, the cleaned substrate is polished to further remove the surface oxide film; Step 23: storing the processed substrate in a vacuum drying oven; Step 3: Solder paste coating Step 31: evenly apply the micron In and nano Cu@Ag core-shell mixed solder paste on the substrate processed in step 4 by screen printing; Step 32: Place the substrate coated with solder paste in a constant temperature drying oven for preheating; Step 4: Hot Pressing and Sintering The chip is placed on the solder paste to form a sandwich structure and placed in a hot press for sintering.

2. The interconnection process of micron In and nano Cu@Ag core-shell hybrid materials according to claim 1 is characterized in that In the step 11, the drying conditions are as follows: drying at room temperature for 4 h under a vacuum condition of -1 MPa; in the step 12, the organic dispersant is one or a mixture of polyethylene glycol-400, ethanol, butanol, ethylene glycol and propylene glycol, the mass percentage of nano Cu@Ag core-shell particles and micron In particles in the mixed powder is 70~95%:5~30%, and the mass percentage of the mixed powder and the organic dispersant in the mixed solder paste is 80~90%:10%~20%.

3. The interconnection process of micron In and nano Cu@Ag core-shell hybrid materials according to claim 1 is characterized in that In the steps 2 and 3, the storage conditions are as follows: storage at room temperature under -1 MPa vacuum conditions.

4. The interconnection process of micron In and nano Cu@Ag core-shell hybrid materials according to claim 1 is characterized in that In the step 31, the coating thickness of the micron In and nano Cu@Ag core-shell mixed solder paste on the substrate is 50-200 μm; in the step 32, the preheating conditions are as follows: preheating at 110-140 °C for 5-30 min.

5. The interconnection process of micron In and nano Cu@Ag core-shell hybrid materials according to claim 1 is characterized in that In the step 4, the sintering conditions are as follows: the heating method adopts double-sided heating, the temperature rise rate is 4-6 ° C / min, the pressure is 1-10 MPa, the heating temperature is 300-400 ° C, and the heating time is 5-30 min.

6. A micron In and nano Cu@Ag core-shell hybrid material interconnection process, characterized in that The process comprises the following steps: Step 1: Preparation of micron In and nano Cu@Ag core-shell mixed solder paste Step 1: Weigh the dried micron In particles, pour them into the nano Cu@Ag core-shell particle solution, centrifuge after ultrasonication and dry them in a vacuum drying oven; Step 1 and 2, placing the dried nano Cu@Ag core-shell particles and micron In particles mixed powder in a mortar, adding an organic dispersant, grinding them fully to make them evenly mixed and grinding them into a paste to obtain a micron In and nano Cu@Ag core-shell mixed solder paste; Step 2: Substrate processing Step 21: Use acetone to remove oil stains on the surface of the substrate, and use dilute hydrochloric acid to remove surface oxides; Step 22: After drying, the cleaned substrate is polished to further remove the surface oxide film; Step 23: storing the processed substrate in a vacuum drying oven; Step 3: Printing of solder paste Place the mask in the center of the substrate, use a medicine spoon to evenly apply the nano-Cu@Ag and micro-In mixed solder paste on the substrate surface, and use a scraper to flatten the solder paste surface and scrape off the excess solder paste to obtain a printed substrate; Step 4: Electromagnetic Induction Sintering The printed substrate and the chip are assembled into a sandwich structure, pressure is applied to the assembled sandwich structure sample, and it is placed on the upper end of the output copper tube of the electromagnetic induction heating equipment for rapid sintering.

7. The interconnection process of micron In and nano Cu@Ag core-shell hybrid materials according to claim 6 is characterized in that In the step 11, the drying conditions are as follows: drying at room temperature for 4 h under a vacuum condition of -1 MPa; in the step 12, the organic dispersant is one or a mixture of polyethylene glycol-400, ethanol, butanol, ethylene glycol and propylene glycol, the mass percentage of nano Cu@Ag core-shell particles and micron In particles in the mixed powder is 70~95%:5~30%, and the mass percentage of the mixed powder and the organic dispersant in the mixed solder paste is 80~90%:10%~20%.

8. The interconnection process of micron In and nano Cu@Ag core-shell hybrid materials according to claim 6 is characterized in that In the steps 2 and 3, the storage conditions are as follows: storage at room temperature under -1 MPa vacuum conditions.

9. The interconnection process of micron In and nano Cu@Ag core-shell hybrid materials according to claim 6, characterized in that In the step three, the thickness of the micron In and nano Cu@Ag core-shell mixed solder paste applied on the substrate is 60-80 μm.

10. The interconnection process of micron In and nano Cu@Ag core-shell hybrid materials according to claim 6, characterized in that In the step 4, the sintering conditions are as follows: the heating power is 24-28KW, the sintering time is 10-30s, and the applied pressure is 1-10MPa.

Citation Information

Patent Citations

  • Method for preparing low-temperature interconnection / high-temperature serving joints by using nano intermetallic compound particles

    CN102922071A

  • Multi-scale Cu@Ag micron-nano composite solder for power device packaging and preparation method

    CN110814569A